Slc6a4 and Htr2a gene Polymorphisms in Malay-Malaysian Schizophrenia - A.Talib, Norlelawati; Abdullah, Nor Zamzila; Aladzemi, Farah Wahida (IIUM Press, International Islamic University Malaysia, 2017)
Schizophrenia (Sz) affect about 21 million people worldwide. This disorder alters perception, thoughts, affect and behaviour. Serotonin (5-Hydroxytryptamine, 5-HT) is a monoamine neurotransmitter which has been hypothesized to be abnormal in schizophrenia. The solute carrier family 6 member 4 (SLC6A4) gene and serotonin receptor 2A (HTR2A) gene are among the important genes within the serotonergic system-related genes family. The SLC6A4 gene encode for serotonin transporter (SERT) which regulates the synaptic concentration of serotonin by transporting serotonin molecules back to the pre-synaptic neuron while the HTR2A gene is another gene that encode for the serotonin receptor subtype 2A. Studies done previously failed to produce consistent result for specific locus of schizohrenia susceptibility